Composition Analysis of Bubu Catches in the Napangga River, Tanjung Medan District, Rokan Hilir Regency - Robby Septian; Isnaniah Isnaniah; Arthur Brown (Tropical Marine Enviromental Sciences, 2023)
This study aims to determine the types of main catches and bycatch and to identify the dominant types and sizes of fish caught. This research was conducted from January to February 2023 in the waters of the Napangga River, Tanjung Medan Village, Tanjung Medan District, Rokan Hilir Regency. The method used in this study was a survey method by directly observing the catch of bubu and then identifying the type of fish, the number of individuals, and the weight of the fish. The results showed that the main catches were two types of fish, namely Kissing gourami (Helostoma temminckii) totaling 30 individuals, and Ompok hypophthalmus totaling 24 individuals. Bycatch caught were 8 types of fish with a total of 47 individuals